Helminth parasites of alien freshwater fishes in Patagonia (Argentina) - Rauque Perez, Carlos Alejandro (2018)
A survey of the helminth parasites of alien freshwater fishes from Argentinean Patagonia is presented, based on samples taken from 2010 to 2017 and including previous published records. A total of 1129 fishes were collected, belonging to 11 species from 7 families. We surveyed 34 localities in 12 river basins, and found 43 parasite taxa (15 digeneans, 14 monogeneans, 5 cestodes, 5 nematodes, and 4 acanthocephalans), belonging to 22 families. Data are presented as a parasite/host list with information on host species and localities, site of infection, parasite life–history stage, origin, previous records in Patagonia, and accession numbers to vouchers. The most frequently found helminths were monogeneans and digeneans. Our data suggest that invading fish in Patagonia have transmitted fewer parasite species than they have received by spillback. Twenty–three (53%) of the parasites seem to be acquired by the exotic fishes from native hosts, while 15 helminths were co–introduced along with their exotic fish host and continue to parasitize these alien fish but did not invade native hosts; 4 of these species were introduced with carp, 3 with Cheirodon interruptus, 3 with Corydoras paleatus, 3 with Cnesterodon decemmaculatus, 1 with Oncorhynchus tshawytscha, and 1 with Jenynsia multidentata. The majority of these co–introduced parasites came from the Brazilic ichthyogeographic region (10 species). This is the first review of helminth parasites of alien fishes in Argentina; in total 12 new records of parasites for Argentina, 6 new records of parasites for Patagonia, and 29 new host–parasite records are presented here. This list is far from complete, however, given that some basins in southern Patagonia remain unexplored in terms of parasite detection.